Selective reinnervation of transplanted muscles by their original motoneurons in the axolotl - Wigston, DJ (J Neurosci, 1987)
The motoneurons innervating 3 hindlimb extensor muscles, anterior and posterior iliotibialis and iliofibularis, were studied separately by retrograde labeling with HRP. The motor pools for these 3 muscles overlapped to such an extent that individual motoneurons between ventral roots 16 and 17 could not be assigned unambiguously to one pool or another. Thus, conventional retrograde labeling could not identify particular axolotl motoneurons. Instead, a double retrograde-labeling technique was employed to mark the motoneurons innervating a particular muscle, the left posterior iliotibialis. Either diamidino yellow (DY) or HRP satisfactorily labeled axolotl motoneurons for at least 3 months in vivo. After labeling, both anterior and posterior iliotibialis muscles were removed from the injected limb and replaced with their counterparts from the opposite limb, in reversed anterior-posterior orientation. Several weeks later, a second marker (DY or HRP) injected into the posterior iliotibialis muscle in its new, more anterior, position labeled the neurons that reinnervated this muscle; the number of neurons labeled with both first and second tracers gave an indication of the selectivity of reinnervation. Using this approach, we have found that the majority of neurons reinnervating a particular muscle are members of that muscle's original motor pool.